1998
DOI: 10.1039/a800548f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protic and aprotic solvents on quenching mechanisms involving dimethyl-substituted donors and tetracyanoquinodimethane (TCNQ)

Abstract: Steady-state and time-resolved spectroscopic techniques have been used to study photoinduced quenching reactions e.g. electron transfer (ET), energy transfer processes etc. between the electron donors 3,5-dimethylphenol (3,5-DMP) and 3,5-dimethylanisole (3,5-DMA) and the electron acceptor TCNQ in polar aprotic acetonitrile (ACN) and polar protic ethanol (EtOH) at ambient temperature. In both solvents photoinduced ET reactions are found to be highly exothermic (*G0 \ [2 eV) and appear, since [*G0 [ j (where j i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…If we compare the PET process in EtOH and DMSO, it is known that the rate of PET is much slower in polar protic solvent EtOH compared to the rate of PET in polar aprotic solvents. 48 The probable reason was cited as the ordered structure of EtOH due to H-bonding. So, in our case, the minimum fluorescence intensity of PPQ-CDs was observed in DMSO, probably due to the efficient PET process in an aprotic solvent devoid of H-bonding.…”
Section: H Nmrmentioning
confidence: 99%
“…If we compare the PET process in EtOH and DMSO, it is known that the rate of PET is much slower in polar protic solvent EtOH compared to the rate of PET in polar aprotic solvents. 48 The probable reason was cited as the ordered structure of EtOH due to H-bonding. So, in our case, the minimum fluorescence intensity of PPQ-CDs was observed in DMSO, probably due to the efficient PET process in an aprotic solvent devoid of H-bonding.…”
Section: H Nmrmentioning
confidence: 99%
“…It was reported that photoinduced electron transfter (PET) between a fluorophore and TCQN can lead to fluorescence quenching. 24 In our present study, the close proximity of FAM dye to TN will lead to fluorescence quenching due to PET between FAM and TN. (2) The hybridization of FAM-labeled ssDNA with its target produces a dsDNA which detaches from TN, leading to fluorescence recovery.…”
Section: Resultsmentioning
confidence: 62%
“…On the contrary, F 4 TCNQ generates a radical anion easily and can be ionized progressively in polar solvents like water but presents good stability and solubility in organic solvents like chloroform. 33,34 Therefore, a complete transfer of Ag NPs from water to chloroform is essential to facilitate the kinetic study, which eliminates the ionization of F 4 TCNQ caused by the aqueous solution itself. Surface modification of Ag NPs is carried out as shown in Scheme 1: thiolated poly(ethylene glycol) (PEG-SH) and dodecanethiol (DDT) are used to modify the surface of silver nanoparticles with a thin surfactant layer (surface coverage of PEG-SH on the Ag NP is at maximum 0.89 nm −2 ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The localized surface plasmon resonance (LSPR) of the Ag NPs in water centers at 400 nm, as shown in Figure b, which is in good agreement with the previous report. , The as-prepared Ag NPs can be well dispersed in aqueous solutions thanks to the hydrophilic citrate-stabilized surface, but aggregate in organic solvents, such as acetonitrile and chloroform (see Figure S1 in the Supporting Information). On the contrary, F 4 TCNQ generates a radical anion easily and can be ionized progressively in polar solvents like water but presents good stability and solubility in organic solvents like chloroform. , Therefore, a complete transfer of Ag NPs from water to chloroform is essential to facilitate the kinetic study, which eliminates the ionization of F 4 TCNQ caused by the aqueous solution itself. Surface modification of Ag NPs is carried out as shown in Scheme : thiolated poly­(ethylene glycol) (PEG-SH) and dodecanethiol (DDT) are used to modify the surface of silver nanoparticles with a thin surfactant layer (surface coverage of PEG-SH on the Ag NP is at maximum 0.89 nm –2 ) .…”
Section: Resultsmentioning
confidence: 99%